MUTU ASPAL BETON PADA RUAS JALAN BLONDO-MENDHUT - Subagyo, Singgih (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The Blondo-Mendut road section is part of the Borobudur National Tourism Strategy Area as the main access to Borobudur Temple tourism destinations and its surroundings, making this road very vital. In the implementation of construction work, quality aspects are targeted in addition to timeliness and cost. Quality control is very important so that at every stage of work can be monitored so that the construction produced is according to predetermined specifications. The study aims to determine the quality of each stage of asphalt concrete work in the laboratory and field and to analyze the results of testing the asphalt concrete pavement layer according to the 2018 Bina Marga technical specification standards. From the results of asphalt concrete testing on the Blondo-Mendut Road Section Rehabilitation project at the Borobudur Magelang KSPN as follows: From the results of examining the aggregates from ex Clereng Kulonprogo, it was found that the average wear and tear was 19.40%, on crushed stone with a diameter of 0.5 max 3/8